z=ln(x+e^(-y))
dz/dx=1/(x+e^(-y))*(x+e^(-y))'=1/(x+e^(-y))
d2z/dx2=((x+e^(-y))^(-1))'=-(x+e^(-y))^(-2)*(x+e^(-y))'=-1/(x+e^(-y))^2
d3z/dx2dy=(-(x+e^(-y))^(-2))'=-(-2(x+e^(-y)))^(-3)*(x+e^(-y))'=2(x+e^(-y))^(-3)*(-e^(-y))=-2e^(-y)/(x+e^(-y))^3
dz/dy=1/(x+e^(-y))*(x+e^(-y))'=1/(x+e^(-y))*(-e^(-y))=-e^(-y)/(x+e^(-y))
d2z/dydx=(-e^(-y)*(x+e^(-y))^(-1))'=-e^(-y)*((x+e^(-y))^(-1))'=
-e^(-y)*(-((x+e^(-y))^(-2)))*(x+e^(-y))'=e^(-y)/(x+e^(-y))^2
d3z/dydx2=(e^(-y)/(x+e^(-y))^2)'=e^(-y)((x+e^(-y))^(-2))'=
e^(-y)*(-2((x+e^(-y))^(-3)))*(x+e^(-y))'=-2e^(-y)/(x+e^(-y))^3
и все
-2e^(-y)/(x+e^(-y))^3-(-2e^(-y)/(x+e^(-y))^3)=-2e^(-y)/(x+e^(-y))^3+2e^(-y)/(x+e^(-y))^3=0
Объяснение:
b2 - b1 = 3
b6 - b5 = 48
S4=?
b2-b1=b1(q -1)=3
b6-b5=b5(q-1)=48
48/3 = (b5/b1)
16=q^4
q=2
b1(q-1)=3
b1*1=3
b1=3
Sn=b1(q^n -1) / q-1
S4 = 3(16-1)/2-1
S4=3*15=45